Solution of Recurrence relation to find a series expression

6 visualizaciones (últimos 30 días)
MINATI
MINATI el 7 de En. de 2020
Editada: MINATI el 7 de En. de 2020
syms x k r f(x) g(x) a b beta b1 M L
syms F(k) G(k)
F(0)=0;F(1)=1;F(2)=a/2;G(0)=0;G(1)=1/2;G(2)=b/2;b1=1/beta;
%%%%dnf=diff(f,x,n)
d1f=(k+1)*F(k+1);d2f=(k+1)*(k+2)*F(k+2);d3f=(k+1)*(k+2)*(k+3)*F(k+3);
d1g=(k+1)*G(k+1);d2g=(k+1)*(k+2)*G(k+2);d3g=(k+1)*(k+2)*(k+3)*G(k+3);
fd2f=symsum(((k-r+1)*(k-r+2)*F(r)*F(k-r+2)),r,0,k);%%% f*d2f
gd2g=symsum((k-r+1)*(k-r+2)*G(r)*G(k-r+2),r,0,k);fd2g=symsum((k-r+1)*(k-r+2)*F(r)*G(k-r+2),r,0,k);
gd2f=symsum((k-r+1)*(k-r+2)*G(r)*F(k-r+2),r,0,k); d1fd1f=symsum((k-r+1)*(r+1)*F(r+1)*F(k-r+1),r,0,k); %%(d1f)^2
d1gd1g=symsum((k-r+1)*(r+1)*G(r+1)*G(k-r+1),r,0,k);
%%%%%%%
eqn1=simplify((1+b1)*d3f-d1fd1f+fd2f+gd2f-(M+L)*d1f==0);
eqn2=simplify((1+b1)*d3g-d1gd1g+fd2g+gd2g-(M+L)*d1g);eqns=[eqn1 eqn2];
solve([eqns,{F(k+3),G(k+2)}])
f=sum(x^k*F(k),k,0,inf);g=sum(x^k*G(k),k,0,inf);
%%%%%%%%%
Using the above code (ofcourse after modification), I want to solve the recurrence relations {F(k+3),G(k+2)} which contains series expression
and using given condition (F(0)=0;F(1)=1;F(2)=a/2;G(0)=0;G(1)=1/2;G(2)=b/2;) to find f and g (SERIES FORM)
OR
the attched pdf (similar problem) can be followed
Thanks

Respuestas (0)

Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!

Translated by